Pillarization, Multiculturalism and Cultural Freezing. Dutch Migration History and the Enforcement of Essentialist Ideas - Schrover, Marlou (BMGN - Low Countries Historical Review, 2010)
During the 1970s, the Netherlands introduced a set of multi-cultural policies which, through government subsidies, subsidised and promoted the otherness of migrants for several decades. Other countries also embraced multiculturalism. In the Netherlands, however, this policy represented a continuation of an older tradition of pillarization. Multiculturalism was not pillarization in new clothes, however, although there was a continuity of the underlying ideas, as this article will show. This led to a great deal of enthusiasm for multiculturalism, and subsequently to great disappointment, without it ever becoming clear what exactly the aim of the policy was and how its success or failure could be measured. The central thesis of this article is that the successive development of pillarization and multiculturalism in the Netherlands has led to a reinforcement of essentialist ideas concerning migrants and their descendants, as well as a freezing of ideas on ‘the’ Dutch culture. This double freezing then made adaptation difficult or impossible. This article is part of the special issue ’The International Relevance of Dutch History’.